The ghosts of ecosystem engineers: Legacy effects of biogenic modifications - Albertson, Lindsey K.; Sklar, Leonard S.; Tumolo, Benjamin B.; Cross, Wyatt F.; Collins, Scott F.; Woods, H. Arthur (Functional ecology, 2024)
Ecosystem engineers strongly influence the communities in which they live by modifying habitats and altering resource availability. These biogenic changes can persist beyond the presence of the engineer, and such modifications are known as ecosystem engineering legacy effects. Although many authors recognize ecosystem engineering legacies, and some case studies quantify the effects of legacies, few general frameworks describe their causes and consequences across species or ecosystem types. Here, we synthesize evidence for ecosystem engineering legacies and describe how consideration of key traits of engineers improves understanding of which engineers are likely to leave persistent biogenic modifications. Our review demonstrates that engineering legacies are ubiquitous, with substantial effects on individuals, communities and ecosystem processes. Attributes that may promote the persistence of influential legacies relate to an engineer's traits, including its body size, life span and living strategy (individual, conspecific group or collection of multiple co‐occurring species). Additional lines of inquiry, such as how the recipients respond (e.g. density or richness) or the mechanism of engineering (e.g. burrowing or structure building), should be included in future ecosystem engineering legacy research. Understanding patterns of these persistent effects of ecosystem engineers and evaluating the consequences of losing them is an important area of research needed for understanding long‐term ecological responses to global change and biodiversity loss. Read the free Plain Language Summary for this article on the Journal blog.